Relation between bruxism and dental implants - TORCATO,Leonardo Bueno (2014)
OBJECTIVE: The aim of this study was to gather information and discuss the predictability of implant-supported prostheses in patients with bruxism by performing a literature review. METHODS: In order to select the studies included in this review, a detailed search was performed in PubMed and Medline databases, using the following key words: bruxism, dental implants, implant supported prosthesis, and dental restoration failure. Items that were included are: case reports, randomized controlled trials, in vitro studies, literature and systematic reviews, with or without meta-analysis, of the last 20 years that addressed the theme. Articles without abstracts, animal studies, articles in languages other than English and articles from journals unrelated to the dental field were excluded. RESULTS: after analysis according to inclusion and exclusion criteria, 28 articles were selected from a total of 54. It is known from the array of scientific articles which have assessed, either through retrospective, prospective or experimental studies, that the biomechanical and biological impact of bruxism on implant-supported prostheses is small, and that the literature has contributed little to exemplify the prosthetic limits of safety for the specialist from a clinical point of view. CONCLUSION: Although there is still no general consensus on this matter, most of the literature review articles do provide clinical guidelines that contribute to implant supported prostheses longevity and stability in patients with bruxism.